Synthesis of CeO2/reduced graphene oxide nanocomposite for electrochemical determination of ascorbic acid and dopamine and for photocatalytic applications. (June 2019) - Murali, A.; Lan, Y.P.; Sarswat, P.K.; Free, M.L.
Abstract: In this study, the CeO2 /reduced graphene oxide (rGO) nanocomposite was synthesized by a facile hydrothermal method. Structure and morphology of the synthesized nanocomposite were characterized by X-ray diffraction and scanning electron microscopy. Raman spectroscopy and X-ray photoelectron spectroscopy were used to quantify the concentration of oxygen vacancies. Compared with the bare glassy carbon electrode (GCE) and CeO2 -modified GCE, the CeO2 /rGO electrode exhibited an excellent electrochemical activity toward the oxidation of ascorbic acid and dopamine. Increased concentration of oxygen vacancies coupled with the introduction of rGO as a matrix in the composite resulted in the improvement of the conductivity of the nanocrystals, thereby leading to a faster charge transfer. The photocatalytic properties of CeO2 and CeO2 /rGO nanocomposite were evaluated using the degradation of methylene blue under UV–vis light irradiation. Degradation rate constant was determined to be 0.0011 min −1 and 0.0035 min −1 with CeO2 and CeO2 /rGO photocatalyst, respectively. The CeO2 /rGO nanocomposite exhibited a significant increase in the photoactivity compared with CeO2 because of the unique properties of rGO in suppressing the recombination of photogenerated charge carriers. Highlights: CeO2 /reduced graphene oxide (rGO) was synthesized by a facile hydrothermal method. CeO2 /rGO exhibited excellent electrocatalytic activity toward ascorbic acid and dopamine oxidation. Increased concentration of oxygen vacancies coupled with rGO resulted in faster charge transfer during the reaction. Presence of rGO as an electron acceptor in the composite facilitated efficient transportation and separation of electron–hole pairs.